ENDOVASCULAR TREATMENT FOR POSTTHROMBOTIC SYNDROME DUE TO UTERINE FIBROIDS - Pinto Sousa, Pedro (2022)
Uterine fibroids are the most common solid pelvic tumors in women, frequently causing hypomenorrhea.They normally do not carry an increased risk for deep venous thrombosis (DVT) unless they reach a considerable size conditioning inferior vena cava and pelvic veins compression.Postthrombotic iliac vein obstructive lesions resulting from a prior episode of DVT may lead to clinical signs and symptoms of chronic vein disease.There is no role for prophylactic treatment of silent lesions. However, if patients develop advanced symptoms (CEAP C3-C6 classification) despite best medical treatment, patients are candidates for endovascular correction with stenting. Endovenous correction of ilio-caval pathology is associated with high technical success rate and reduced complications, around 0.4%.The authors describe a clinical case of a 47 years-old female patient that developed post-thrombotic syndrome due to a DVT, caused by compression from a large uterine fibroid, treated with endovascular surgery.